Mining cytochrome p450 genes through next generation sequencing and metagenomic analysis from Binh Chau hot spring - Tung, Nguyen Van; Hoang, Nguyen Huy; Thoa, Nguyen Kim (Academia Journal of Biology, 2019)
Cytochrome P450s (CYPs) are one of the largest distributed enzymes, which catalyze more than 20 different reactions. At present, there has been an increasing realization of the power of P450 biocatalysts for the industrial synthesis of pharmaceuticals, agrochemicals, bulk chemicals, food ingredients, etc. On the other hand, the conditions of industrial processes at high temperature, high-pressure or in chemical solvent require the enzymes, which catalyze the bioconversion, have a specific properties such as thermostability, chemical tolerance or barophilicity. Up to date, the number of thermostable P450s is limited. Nowadays, DNA-metagenome technique gives us a chance to catch novel genes and unique interesting enzymes from microbial community in certain ecology. In this paper, metagenomic DNA extracted from water samples from Binh Chau hot spring was sequenced using Illumila’s HiSeq platform and was analysed to mining putative genes encoding cytochrome P450. The sequencing generated 9.4 Gb of reads containing 156,093 putative ORFs, of these, 106,903 genes were annotated in NCBI non-redundant protein sequence database. Among all the ORFs were annotated, 68 putative ORFs encoding cytochrome P450 were found belong to 36 specific groups of cytochrome P450 protein family. Of these, the melting temperature (Tm) from thirty-six completed ORFs was predicted for a better understanding of thermodynamic stability.